A monoterpene antioxidant, linalool, mitigates benzene-induced oxidative toxicities on hematology and liver of male rats. Issue 1 (1st January 2021) - Ola, Olaniyi Solomon; Sofolahan, Temitope Ayooluwa
ABSTRACT: Benzene is a volatile chemical implicated in leukemia and hepatic injury through oxidative stress-mediated mechanism. Linalool is a naturally small molecular monoterpene with proven antioxidant properties. This study was carried out to investigate the potential role of Linalool in ameliorating the oxidative stress-mediated hematologic and hepatic dysfunctions by Benzene in rats. Hepatic injury and hematological imbalance were induced in Wister rats by intravenous administration of 0.2 mL of benzene solution every other days for 3 consecutive weeks. Following benzene intoxication, 40 mg/kg linalool was post-administered each day orally for two weeks. Hematological alteration was assessed by comparing the hematological parameters of control and benzene-exposed animals with or without linalool supplementation. Plasmal activities of liver biomarker enzymes (ALT, AST, and ALP), total thiol and advanced oxidation protein products (AOPPs) along with hepatic activities of SOD, CAT, and hepatic contents of thiol-reduced glutathione (GSH), malondialdehyde, and percentage DNA fragment were measured. Linalool showed improvements in liver functions and restored altered hematology, decreased levels of AOPPs and oxidative stress and mitigated genotoxicity affected by benzene. In conclusion, linalool exerted its organ protective and myeloprotective effect through its influence on antioxidant defense system and reduction of oxidative stress.